Clinical Significance of Pancreatic Fat in Children: A Single-Center Experience. Issue 8 (September 2022) - Cho, Jin Young; You, Sun Kyoung; Lim, Han Hyuk; Kim, Hyun Jin
Abstract : Objectives: Recently, interest in pancreatic fat has increased, and fatty pancreas is considered to be related to nonalcoholic fatty liver disease (NAFLD) and metabolic syndrome. We aimed to evaluate the prevalence of echogenic pancreas in children and its related factors. Methods: We retrospectively analyzed the data of patients aged 5 to 18 years who had undergone abdominal sonography between January 2020 and December 2020. Patients with chronic or pancreatic diseases were excluded. Results: Of 102 patients, 27 (26.5%) had echogenic pancreas and 55 (53.9%) had NAFLD. Among the 55 patients with NAFLD, 18 (32.7%) had an echogenic pancreas. Patients with echogenic pancreas had significantly higher fasting glucose, low-density lipoprotein cholesterol, and triglyceride levels than those without echogenic pancreas. The proportion of NAFLD and obesity was higher in the echogenic group; however, only the proportion of obese subjects showed a significant difference. In multivariate analysis, family history of diabetes mellitus (DM) and/or dyslipidemia and presence of DM and/or dyslipidemia were factors related to the presence of echogenic pancreas. Conclusions: Echogenic pancreas is relatively common in children. Echogenic pancreas, typically observed in patients with a family history of DM and/or dyslipidemia, was strongly associated with metabolic syndrome, even in the absence of fatty liver.